Endometrial angiogenesis induced by uterine insufflation with an oxygen–ozone gas mixture in mares - Camargo Ferreira, Jair; Silva Amaral, Rafael; Mara Cardoso, Letícia; Panelli Marchió, Sophia; Aldrovani Rodrigues, Marcela; Fonseca Alves, Carlos Eduardo [UNESP]; de Meira, Cezinande [UNESP] (Wiley, 2021)
Ozone (O3) therapy has been used to improve peripheral tissue oxygenation in humans and domestic animals. The goal of the present study was to characterize histological changes in the endometria of healthy equines following tissue exposure to gas mixtures enriched with different concentrations of O3. Cycling mares without endometrial degeneration were divided into three groups according to treatment (n = 9 mares/group). The uteri from the O3, ½O3 and control groups were insufflated for 3 min with gas containing 42, 21 and 0 μg O3 ml-1, respectively. Treatments were performed every three days from D0 to D6. Endometrial samples were collected immediately before the first treatment and 24 hr after the last treatment. The following nine histological parameters were evaluated: (i) the number of endometrial blood vessels, (ii) endometrial vascular degree (EVD), (iii) increase rate of blood vessels, (iv) increase rate of EVD, (v) glandular total area, (vi) glandular lumen area, (vii) intraglandular secretion area, (viii) glandular epithelial height and (ix) luminal epithelial height. In the O3 group, a positive effect from treatment (p <.01) was detected for all vascular parameters (i, ii, iii and iv), glandular total area, intraglandular secretion area and glandular epithelial height. Compared to the control group, the ½O3 group had greater (p <.01) EVD (84.1 ± 12%) and a higher increase rate of blood vessels (151.9 ± 47.1%). Uterine insufflation with low or intermediate concentrations of the O2–O3 gas mixture induced endometrial angiogenesis. Morphometry, but not morphology, of the endometrial glands was affected by local O3 therapy. These findings would be of great significance for the development of new therapies for infertility in mares.
Keywords: blood flow; endometrial gland; horse; ozone therapy; uterus